A systematic review of the application of augmented reality (AR) technology for the visualization and management of digital assets in libraries - Farida, Ismi Anjar; Kurniasih, Nuning; Kusnandar (Record and Library Journal, 2025)
Background of the study: In today’s libraries, increasing pressures on managing and visualizing digital collections in an efficient, interactive, and user-centered way continue to challenge the profession. Augmented Reality (AR) holds promise to facilitate spatial navigation, access to collections, and learning experiences in libraries. Purpose: The purpose of this research is to conduct a systematic review of the literature related to AR applications in library digital collections, visualization, and management. Method: Using a Systematized Literature Review (SLR) methodology, articles were found through the Publish or Perish software using Google Scholar as the primary search engine. A total of 100 articles were initially screened, and 36 articles that met predefined inclusion and exclusion criteria were selected for in-depth thematic analysis to uncover emerging patterns and research clusters. Findings: Five main themes were identified: 1) Augmented Reality (AR) for Library Navigation and Orientation, 2) AR for Visualization of Digital Assets: AR is increasingly investigated as a medium for the visualization of digital collections, 3) Integration of AR with Complementary Technologies, 4) Application of AR in Specialized Library Contexts, and 5) AR as a Facilitator of Educational Objectives. The most significant challenges identified include limited infrastructure, difficulties with system integration, and training/education issues for librarians. Conclusion: This review confirms the high potential for AR to improve user engagement, facilitate information connectivity, and enhance educational functions within libraries. However, the success of AR relies on broadband infrastructure, open content, and partnerships across community sectors, with implications for both theory and the development of immersive services.